Review of First Principles Simulations of STO/BTO, STO/PTO, and SZO/PZO (001) Heterostructures - Eglitis, Roberts I.; Bocharov, Dmitry; Piskunov, Sergei; Jia, Ran (MDPI, 2023)
In this study, we review our first-principles simulations for STO/BTO, STO/PTO, and SZO/PZO (001) heterostructures. Specifically, we report ab initio B3PW calculations for STO/BTO, STO/PTO, and SZO/PZO (001) interfaces, considering non-stoichiometric heterostructures in the process. Our ab initio B3PW calculations demonstrate that charge redistribution in the (001) interface region only subtly affects electronic structures. However, changes in stoichiometry result in significant shifts in band edges. The computed band gaps for the STO/BTO, STO/PTO, and SZO/PZO (001) interfaces are primarily determined according to whether the topmost layer of the augmented (001) film has an AO or BO2 termination. We predict an increase in the covalency of B-O bonds near the STO/BTO, STO/PTO, and SZO/PZO (001) heterostructures as compared to the BTO, PTO, and PZO bulk materials. --//-- This is an open access article R.I. Eglitis*, D. Bocharov, S. Piskunov, R. Jia; Review of first principles simulations of STO/BTO, STO/PTO, and SZO/PZO (001) heterostructures; Crystals, 2023, 13, 799 (pp. 1-25); DOI: 10.3390/cryst13050799; https://www.mdpi.com/2073-4352/13/5/799 published under the CC BY 4.0 licence.
We acknowledge the financial support from our funder the Latvian Council of Science. The funding number is Grant No. LZP-2020/1-0345. The Institute of Solid-State Physics, University of Latvia (Latvia), as a center of excellence, has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD01-2016-2017-Teaming Phase 2 under Grant Agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; STO/BTO (001) interface; STO/PTO (001) heterostructure; SZO/PZO (001) interface; Γ-Γ band gap; B-O bond covalency